The Effectiveness of Reproductive Health Counseling for Pregnant Adolescents in Preventing High-Risk Pregnancies - Ziadatul Munawarah; Olyvia Rosalia (Oshada, 2025)
This study aimed to evaluate the effectiveness of reproductive health counseling in improving knowledge, attitudes, and health outcomes among pregnant adolescents, as well as its role in preventing high-risk pregnancies. A quasi-experimental design was used with two groups: an experimental group receiving structured counseling sessions and a control group receiving standard care. Data were collected through pretest and posttest questionnaires assessing reproductive health knowledge and attitudes, along with medical indicators such as maternal hemoglobin levels, blood pressure, and neonatal birth weight. The results showed a significant improvement in knowledge and positive changes in attitudes among participants in the counseling group compared to the control group. Furthermore, health outcomes such as reduced incidence of anemia and low birth weight were more favorable in the experimental group. These findings indicate that reproductive health counseling is an effective intervention for reducing pregnancy risks and promoting maternal and child health. The study supports integrating adolescent-focused counseling into primary healthcare services to address the unique challenges faced by pregnant teenagers and to improve overall reproductive health outcomes.